Study of Effects on Performances and Emissions of a Large Marine Diesel Engine Partially Fuelled with Biodiesel B20 and Methanol - Nicolae Adrian Visan; Dan Catalin Niculescu; Radu Ionescu; Ernst Dahlin; Magnus Eriksson; Radu Chiriac (Journal of Marine Science and Engineering, 2024)
The impact of fossil fuel utilisation in different combustion systems on climate change due to greenhouse gas accumulation in the atmosphere is rather evident. A part of these gases comes from the large engines used for propulsion in marine applications. In the continuous global effort made by engine manufacturers to mitigate this negative impact, one way is represented by the utilisation of alternative fuels such as biodiesel and methanol, based on dedicated research to fulfil the more stringent regulations concerning pollutant emissions issued by piston heat engines. In this study, a numerical investigation was conducted on a four-stroke large marine diesel engine (ALCO 16V 251C) at several engine speeds and full load conditions. Different blends of diesel–methanol and biodiesel B20–methanol with methanol mass fractions of 10% and 20% were considered for theoretical analysis in two techniques of methanol supply: direct injection mode of a blend of base fuel diesel/biodiesel B20 with methanol and injection of methanol after the intercooler, and direct injection of the base fuel. The results show that, if 10% in power loss can be acceptable, then for diesel–methanol 10%, in the direct injection technology, the NOx emission can be reduced up to 19%, but with a compromise of an 8% increase in SOOT emission, while for biodiesel B20–methanol 10%, with the same direct injection method, the NOx emissions increase by up to 58% with the benefit of reducing SOOT by up to 23% relative to the original diesel fuel operation. For a 20% methanol fraction in blend fuel, the drop in power is more than 10% regardless of the method of methanol supply and the base fuel, diesel, or B20 used.